In-service training in preparing NESTs and NNESTs - Hall, Stephen J. * (John Wiley & Sons, 2018)
In-service training whether for native English speakers or non-native English speakers has seen a shift beyond a technical approach to greater ownership of the process by teachers. Issues abound in acceptance of so-called non-native speakers as teachers, yet commonalities exist in the profession when building expertise. Research has shown limited success with large-scale transmission techniques as a focus of professional development. This has led to adoption of reflective practice and group approaches. Pedagogy may also be used as a vehicle for teachers’ own language development and it is in this area that differences which exist between non-native English-speaking teachers (NNESTs) and native English-speaking teachers (NESTs) will be described. However, the core of success could well be in the teacher and teacher educator’s relationship to drive acceptance of what could be novel techniques. Indicators of acceptance of change suggest that a collegial supportive approach through reflection and mentoring may be more beneficial than earlier approaches.